Buruli Ulcer and Medical Geo-Microbiology - Manilal A; Tadesse D; Sabu KR (Infection and Drug Resistance, 2022)
Aseer Manilal,1 Dagimawie Tadesse,1 Kuzhunellil Raghavanpillai Sabu2 1Department of Medical Laboratory Sciences, College of Medicine and Health Sciences, Arba Minch University, Arba Minch, Ethiopia; 2Department of Chemistry, College of Life Sciences, Arba Minch University, Arba Minch, EthiopiaCorrespondence: Aseer Manilal, Email aseermanilal@gmail.comAbstract: Buruli ulcer is a chronic debilitating infectious disease caused by the pathogen Mycobacterium ulcerans, which can be cured if diagnosed and treated in an early stage. However, advanced cases need antibiotic treatment followed by surgical interventions. In this context, an extremely effective and less expensive treatment modality can be developed by means of an extended topical application of certain selected natural clay minerals, most of the time containing illite-smectite having some iron content. There is a scope for developing the speciality, medical geo-microbiology, which is truly a multidisciplinary one, for finding a cure for the severe and advanced cases of BU.Keywords: Buruli ulcer, clay minerals, drug resistance